1999
DOI: 10.1038/14339
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarrays detect activation of a myogenic transcription program by the PAX3-FKHR fusion oncogene

Abstract: Alveolar rhabdomyosarcoma is an aggressive pediatric cancer of striated muscle characterized in 60% of cases by a t(2;13)(q35;q14). This results in the fusion of PAX3, a developmental transcription factor required for limb myogenesis, with FKHR, a member of the forkhead family of transcription factors. The resultant PAX3-FKHR gene possesses transforming properties; however, the effects of this chimeric oncogene on gene expression are largely unknown. To investigate the actions of these transcription factors, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 14 publications
4
94
0
6
Order By: Relevance
“…SLUG expression is being increasingly recognized as an alteration in mesenchymal tumours (both leukaemias and sarcomas) (Inukai et al, 1999;Khan et al, 1999, and this paper), suggesting that SLUG may be a critical factor in tumour invasion not only of BCR-ABL-positive leukaemias but also potentially in other mesenchymal cancers. To show whether SLUG is required for BCR-ABL leukaemogenesis, we demonstrate that the leukaemogenic capacity of BCR-ABLp190 oncogene is dependent on the presence of Slug, indicating that Slug has a fundamental role in the biology of BCR-ABL cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SLUG expression is being increasingly recognized as an alteration in mesenchymal tumours (both leukaemias and sarcomas) (Inukai et al, 1999;Khan et al, 1999, and this paper), suggesting that SLUG may be a critical factor in tumour invasion not only of BCR-ABL-positive leukaemias but also potentially in other mesenchymal cancers. To show whether SLUG is required for BCR-ABL leukaemogenesis, we demonstrate that the leukaemogenic capacity of BCR-ABLp190 oncogene is dependent on the presence of Slug, indicating that Slug has a fundamental role in the biology of BCR-ABL cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Slug is a member of the Snail family of zinc-finger transcription factors that share an evolutionarily conserved role in mesoderm formation in invertebrates and vertebrates (Nieto, 1994(Nieto, , 2002Sefton et al, 1998), In human and mouse, much of the knowledge regarding the function of SLUG has been derived from analysis of loss-of-function mutations (Jiang et al, 1998;PerezLosada et al, 2002;Sanchez-Martin et al, 2002, which have demonstrated that SLUG is critical for development of neural crest-derived cell lineages and from insights into the interaction of SLUG with specific oncogenes in human cancer, notably BCR-ABL (Inukai et al, 1999;Khan et al, 1999, and this manuscript). However, little is known as to how overexpression of SLUG might contribute to malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, constitutive activation of c-kit could confer radioresistance properties to the tumor cells. Moreover, recent findings show that Slug is also expressed in t(17;19) leukemic cells (Inukai et al, 1999), in rhabdomyosarcoma cells expressing the translocation PAX3-FKHR (Khan et al, 1999), and in cells expressing BCR-ABL (JPL et al, unpublished observations). Thus, Slug may be a common component providing radioresistance to tumor cells.…”
Section: Importance Of the Slug-dependent Radioresistance In Cancer Tmentioning
confidence: 99%